Formyl peptide receptor type 2 (FPR2) deficiency in myeloid cells amplifies sepsis-induced cardiac dysfunction - Jianmin Chen; Shani Austin-Williams; Caroline Elizabeth O'Riordan; Pol Claria-Ribas; Michelle A Sugimoto; Lucy V Norling; Christoph Thiemermann; Mauro Perretti (Karger Publishers, 2023)
Using a global formyl-peptide receptor (Fpr)2 knockout mouse colony, we have reported the modulatory properties of this pro-resolving receptor in polymicrobial sepsis. Herein, we have used a humanized FPR2 (hFPR2) mouse colony bearing an intact or a selective receptor deficiency in myeloid cells to dwell on the cellular mechanisms. hFPR2 mice and myeloid cell-specific hFPR2 KO (abbreviated to KO) mice were subjected to cecal ligation and puncture (CLP)-induced polymicrobial sepsis. Compared with hFPR2 mice, CLP caused exacerbated cardiac dysfunction (assessed by echocardiography), worsened clinical outcome and impaired bacteria clearance in KO mice. This pathological scenario was paralleled by increased recruitment of pro-inflammatory monocytes and reduced M2-like macrophages within the KO hearts. In peritoneal exudates of KO mice, we quantified increased neutrophil and MHC II+ macrophage numbers, but decreased monocyte/macrophage and MHC II- macrophage recruitment. hFPR2 up-regulation was absent in myeloid cells and local production of lipoxin A4 was reduced in septic KO mice. Administration of the FPR2 agonist Annexin A1 (AnxA1) improved cardiac function in hFPR2 septic mice, but had limited beneficial effects in KO mice, in which the FPR2 ligand failed to polarize macrophages towards an MHC II- phenotype. In conclusion, FPR2 deficiency in myeloid cells exacerbates cardiac dysfunction and worsens clinical outcome in polymicrobial sepsis. The improvement of cardiac function and the host immune response by AnxA1 is more effective in hFPR2 competent septic mice.